Stanley's Christmas adventure - Brown, Jeff, 1926-2003.; Nash, Scott, 1959- (New York : Scholastic, 2003)
When Santa quits his job a few days before Christmas because of too many greedy children, his daughter whisks young Stanley Lampchop and his family off to the North Pole to help change the old man's mind.
"This edition is only available for distribution through the school market"--Cover.
420
Keywords: Santa Claus -- (Fictitious character) -- Juvenile fiction; Santa Claus -- (Fictitious character) -- Fiction; Christmas -- Fiction